Sex differences in residency patterns of Risso's dolphins (Grampus griseus) in the Azores: Causes and management implications. Issue 3 (1st April 2015) - Hartman, Karin Louise; Fernandez, Marc; Wittich, Anja; Azevedo, José Manuel N.
Abstract Knowledge of the residency patterns of marine mammals is an important element for management and conservation strategies. Here we investigate a population of Grampus griseus off Pico Island, Azores. Our data set covers the period 2004–2007, based on at‐sea observations of 1, 250 individually identified animals, 303 of known or assumed sex. Using photo identification and GPS locations we calculated mean monthly sighting rates and lagged identification rates to analyze temporal patterns, and estimated kernel density to study the home range. Our results show site fidelity and relatively restricted home ranges, which corroborate the existence of a resident population on the study site. We further document sex differences, including a higher number of males present in the area at any given time but females staying for longer consecutive periods, and male home ranges with significantly less overlap than those of females. These observations are consistent with a mating system based on multimale pods defending areas where females periodically return. We hypothesize that squid distribution is a major factor in structuring these patterns. These findings reinforce the need for a precautionary management approach that would include limiting pressure from commercial activities.